Early Marriage Determination of Teenagers in Banten Province - Uswatun Hasanah; Rita Dwi Pratiwi; Riris Andriati; Deden Gumilar Nugraha (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Based on the results of the Program Performance and Accountability Survey in Banten year of 2019, the number of births in Banten province at the age of 15-19 years old was still quite high compared to other provinces, namely 39.5% compared to Jakarta City, (25.4%), West Java (25.3%) and East Java (25.9%). The purpose of this study was to identify the determinants of early marriage in Banten Province, used secondary data, namely Program Performance Monitoring and Accountability Survey in 2019. The population in this study were all married women in the 2019, which amounted to 1687 samples. The results of the study were of 1687 respondents. More than 50% of respondents got married at an early age, namely 909 respondents (53.9%). More than 50% respondents had 15-19 years old of first marriage age of 37.1%, their educational background was primary school of 37.8%. The respondents’ occupation were housewives of 75.7% . Based on the bivariate analysis, it showed that the CI was 95%, and the P-value <0.05 showed that there was a significant correlation between education (0,000), socio economic (0.010), and ethnic (0.000), with early marriage based on the analysis of Program Performance and Accountability Survey in 2019. However, there was no significant correlation between occupation and p-value 0.614 at 95% CI. Based on multivariate analysis using logistic regression, it produced the final modeling in determining the determinants of early marriage. The conclusion of these, four determinants showed that educational factors were very influential in early marriage.